Réponses

2014-06-02T17:58:29+02:00
A=-3(-12,5+2a)
  = -3×(-12,5) -3×2a
  = 37,5 -  6a

B=-5(8x-6)
   = -5×8x -5×(-6)
   = -40x + 30

C=(-t+5)(-12)
   = -t×-12 -12×5
   = 12t - 60

D=0,4(-12x + 6)
   = 0,4×(-12x) + 0,4×6
   = 4.8x + 2.4

E=-4/3(3a-6)
   = - \frac{4}{3}  × 3a - \frac{4}{3}  × (-6)
   = -4a + 8

F=11/6y(24y-2)
  = 
 \frac{11}{6y}  × 24y +  \frac{11}{6y}  × (-2)
  = 44y² - 3.6

je ne suis pas sur que ça soit juste au deux dernier
2014-06-02T17:59:44+02:00
A=-3(-12,5+2a)=-3x(-12,5)-3x2a=37,5-6a
B=-5(8x-6)=-40x+30
C=(-t+5)(-12)=12t-60
D=0,4(-12x+6)=-4,8x+2,4
E=-4/3(3a-6)=-4a+8
F=11/6y(24y-2)=11/6yx24y-11/6yx2=11x4-11/3y